TENDENCY OF ADHESIVE PARTICLES ON THE LIQUID WALL LAYER IN THE TURBULENT FLOW CHANNEL - Priambodo, Trisaksono B; SUZUKI, Akira; AOKI, Hideyuki; MIURA, Takatoshi (Agency for the Assessment and Application of Technology)
The experimental investigation and simulation model approach were carried out to investigate the behavior of the fine particles to ad here on the layer of liquid on the wall in gas-solid two-phase flow. Polymethyl methacrylate having two different mean-diameters of 20 mm and of 50mm was used for measurement. By using continuous feeding sys tem, the fine particles were entrained and mixed with the air in the duct. Experiment for solid particle gas with two-phase flow in room temperature was carried out to make a clear turbulent effect for particle adhering behavior to wall side having a high-viscosity liquid layer. These phenomena were also investigated by the simulation model which represented the experimental condition for two-phase flow and using k- two equation models for turbulent flow. The experimental result showed that adhered particle quantity depends on particle feeding rate. The result of simulation model also showed the same tendency. The relation of the various particles feeding rate and capture rate were also described.